Theory, Post-theory, Neo-theories: Changes in Discourses, Changes in Objects - Casetti, Francesco (Cinémas, 2007)
AbstractOver the past ten years, film theory has been openly challenged by the tenets of film history, cultural studies, aesthetics and philosophy. The decline of so called “Grand Theory” has made possible the emergence of a new paradigm. This relative eclipsing of film theory is the sign of a three-fold problem within cinema studies. First, film in its new formats and with its new supports is no longer a unique and consistent object which can be subjected to specific forms of research. Film theory’s weakness is thus a sign that “film,” as an object, is now dispersed. Second, cinema has always been at the crossroads of a great number of different fields. Its history is an amalgam of the history of media, the performing arts, visual perception, modern forms of subjectivity, etc. Film theory’s weakness is symptomatic of the urgent need to rethink a history that was never unique or unified. Third, in our post-modern era any recourse to rationality seems to be a trap, the object of study itself being refractory to any kind of schematization. Film theory’s weakness is indicative of the need to maintain an open approach to the subject. Through these three issues, we are witnessing the emergence of a new theory, both informal and dispersed, which is manifested in a variety of discourses that are content to gloss the phenomenon in order better to understand the cinema and facilitate its social recognition.